Yield evaluation of nutrient-rich potato clones in high hill of Nepal - Luitel, B.P.; Khatri, B.B.; Lama, L.; Dhakal, R.; Khadka, K.; Choudhary, D.; Arya, S.; Kadian, M.S.; Bonierbale, Merideth W. (Nepal Journals Online, 2017)
A study was conducted to evaluate the yield of nutrient-rich potato clones in high-hill districts: Dolakha and Jumla of Nepal during the years 2013 and 2014, respectively. Fourteen potato clones were tested as on-station and on-farm experiments at both districts, and those fourteen clones were compared to 'Lady Rosita' and 'Jumli Local' respectively as the check varieties in the first year experiment, 2013. Eight promising clones were selected from the first year experiment, and were evaluated and compared with same local varieties in the consecutive year, 2014. Two clones namely; CIP 395112.32 (19.3 tha<sup(-1)>) and CIP 393073.179 (17.8 tha<sup(-1)>) exhibited superior marketable tuber yield than that of 'Lady Rosita'(14.2 tha<sup(-1)>) in Dolakha and five CIP clones namely; 395112.32 (25.5 tha<sup(-1)>), 393073.179 (22.5 tha-1), 394611.112 (20.9 tha-1), 390478.9 (19.9 tha<sup(-1)>) and 395017.229 (17.0 tha<sup(-1)>) showed higher marketable tuber yield than 'Jumli Local'(14.5 tha<sup(-1)>). Based on two years' phenotypic and tuber yield result, clones CIP 395112.32 and CIP 393073.179 are recommended to potato growers at high hills of Nepal for commercial cultivation.